Assessment of Radiation Hazard Indices due to Natural Radionuclides in Soil and Vegetation Samples at Federal University Dutsin-Ma, Katsina, Nigeria - Yahaya, Abubakar Aliero; Namadi, Abdulrahman Zuru; Matazu, Muhammed Bako (FUDMA Journal of Sciences, 2026)
Naturally occurring radioactive materials (NORMs) like Potassium-40, Radium-226, and Thorium-232 are commonly found in rocks, soils, and plants. Monitoring these radionuclides in the environment is vital for evaluating human exposure, especially in institutions and residential settings. Excessive Radium-226 causes anaemia, cataracts, and bone cancer, due to its deposition in bone tissue after exposure. (ATSDR, 1990; IAEA, 2015). Thorium-232, poses a significant risk of respiratory diseases, including lung cancer, and may lead to genetic mutations in body cells over time (ATSDR, 1990; ICRP, 2008) Potassium-40, could result in hyperkaliemia, contributing to metabolic disorders, kidney diseases, and diabetes (UNSCEAR, 2000). This study determined the concentrations of ⁴⁰K, ²²⁶Ra, and ²³²Th in soil and vegetation samples at the Federal University Dutsin-Ma main campus using gamma spectroscopy. In soil, activity concentrations ranged from 20.36–47.86 Bq/kg for ²²⁶Ra, 21.03–64.57 Bq/kg for ²³²Th, and 81.56–234.84 Bq/kg for ⁴⁰K, with means of 33.43, 43.16, and 164.32 Bq/kg, respectively. Compared to UNSCEAR global averages, ²²⁶Ra and ²³²Th were slightly higher, while ⁴⁰K was lower. In vegetation, values ranged from 13.73–43.91 Bq/kg (²²⁶Ra), 16.67–50.96 Bq/kg (²³²Th), and 19.63–75.61 Bq/kg (⁴⁰K), with averages of 25.06, 33.10, and 37.30 Bq/kg. All radiological hazard indices (Raeq, Hin, Hex, Iγ, Iα) in both media remained below international safety limits. Soil Raeq ranged from 62.90–158.28 Bq/kg (mean: 107.80 Bq/kg), and vegetation Raeq from 40.23–108.94 Bq/kg (mean: 75.27 Bq/kg). Although vegetation from the Faculty of Life Sciences exhibited higher uptake, overall radiological risk is minimal.